Design and synthesis of hierarchical BxCyNz nanotube composites - McGurty, D (2023)
The sub-class of carbonaceous nanomaterials, borocarbonitride nanotubes, have previously demonstrated encouraging performance with regard to a range of applications which include energy storage, electrocatalysis and environmental remediation. The promise they possess makes them suitable candidates for the development of, novel, next-generation hierarchical nanomaterials. Despite this, the field surrounding them has lacked substantial investigation into their further processing. This thesis looks to address some of the current shortcomings within the field and investigates processing techniques for the functionalisation and macroscopic arrangement of borocarbonitride nanotubes.